2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944348
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary evaluation of an Android based heart rate variability biofeedback system

Abstract: The reduced Heart Rate Variability (HRV) is believed to be associated with several diseases such as congestive heart failure, diabetes and chronic kidney diseases (CKD). In these cases, HRV biofeedback may be a potential intervention method to increase HRV which in turn is beneficial to these patients. In this work, a real-time Android biofeedback application based on a Bluetooth enabled ECG and thoracic electrical bioimpedance (respiration) measurement device has been developed. The system performance and usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The device, is designed by Z-Health Technologies AB and has been used in previous studies [1,2], it measures both Electrocardiogram (ECG) and respiration activity. For this study the sampling frequency is set to 300 Hz for both ECG/EBI and thoracic EBI is done with the injecting current at 50 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The device, is designed by Z-Health Technologies AB and has been used in previous studies [1,2], it measures both Electrocardiogram (ECG) and respiration activity. For this study the sampling frequency is set to 300 Hz for both ECG/EBI and thoracic EBI is done with the injecting current at 50 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…As a part of a project to evaluate Heart Rate Variability (HRV) biofeedback intervention by using a developed Android application [1], we have observed the stress of putting traditional ECG electrodes and associated cables as a threat which may cover the underling improvement in balance of autonomic nervous system i.e. higher HRV and lower heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid technological advances have made applications in smartphones as a potential tool to improve adherence to treatment [15,16]. Several studies have been conducted to prove information technology-based interventions improve self-management and compliance behavior in patients with chronic illness [17]. Based on the above problems, the researchers are interested in conducting research into the development of discharge planning with an Android-based automatic fluid management reminder.…”
Section: Introductionmentioning
confidence: 99%
“…Pace breathing and heart rate variability (HRV) analysis are common aspects of biofeedback training (Lehrer, Vaschillo et al 2000). In Abtahi et al (Abtahi, Berndtsson et al 2014) a real-time application running on an Android phone collects and processes the measurements recorded using wearable sensors to provide users with HRV parameters and respiration rate during pace breathing training sessions. The ECGZ2 unit and the sensorized textile electrode vest garment presented in this research work are used in (Abtahi, Berndtsson et al 2014).…”
Section: Biofeedbackmentioning
confidence: 99%
“…In Abtahi et al (Abtahi, Berndtsson et al 2014) a real-time application running on an Android phone collects and processes the measurements recorded using wearable sensors to provide users with HRV parameters and respiration rate during pace breathing training sessions. The ECGZ2 unit and the sensorized textile electrode vest garment presented in this research work are used in (Abtahi, Berndtsson et al 2014). In their publication, they use the system on eight healthy volunteers to evaluate the system performance and usability, resulting in a biofeedback game ( A concise review of wearable systems for physiological measurements can be found in Hännikäinen et al (2007).…”
Section: Biofeedbackmentioning
confidence: 99%